Preoperative Score to Predict Postoperative Mortality (POSPOM): Derivation and Validation. (March 2016) - Le Manach, Yannick; Collins, Gary; Rodseth, Reitze; Le Bihan-Benjamin, Christine; Biccard, Bruce; Riou, Bruno; Devereaux, P.J.; Landais, Paul
Abstract : Background: An accurate risk score able to predict in-hospital mortality in patients undergoing surgery may improve both risk communication and clinical decision making. The aim of the study was to develop and validate a surgical risk score based solely on preoperative information, for predicting in-hospital mortality. Methods: From January 1, 2010, to December 31, 2010, data related to all surgeries requiring anesthesia were collected from all centers (single hospital or hospitals group) in France performing more than 500 operations in the year on patients aged 18 yr or older (n = 5, 507, 834). International Statistical Classification of Diseases, 10th revision codes were used to summarize the medical history of patients. From these data, the authors developed a risk score by examining 29 preoperative factors (age, comorbidities, and surgery type) in 2, 717, 902 patients, and then validated the risk score in a separate cohort of 2, 789, 932 patients. Results: In the derivation cohort, there were 12, 786 in-hospital deaths (0.47%; 95% CI, 0.46 to 0.48%), whereas in the validation cohort there were 14, 933 in-hospital deaths (0.54%; 95% CI, 0.53 to 0.55%). Seventeen predictors were identified and included in the PreOperative Score to predict PostOperative Mortality (POSPOM). POSPOM showed good calibration and excellent discrimination for in-hospital mortality, with a c -statistic of 0.944 (95% CI, 0.943 to 0.945) in the development cohort and 0.929 (95% CI, 0.928 to 0.931) in the validation cohort. Conclusion: The authors have developed and validated POSPOM, a simple risk score for the prediction of in-hospital mortality in surgical patients. Abstract : This multicenter study examining in-hospital mortality in over 5.5 million patients in France in a 1-yr period identified a 17-variable, highly sensitive, and specific risk calculator for in-hospital mortality.Supplemental Digital Content is available in the text.